The effects of cyclooxygenase inhibitors on the gastric emptying and small intestine transit in the male rats following traumatic brain injury - Keshavarzi, Zakieh (Mashhad University of Medical Sciences, 2014)
OBJECTIVE(S): This study was carried out to investigate the effects of COX-2 selective inhibitor (Celecoxib) or non-selective COX inhibitor (Ibuprofen) on gastrointestinal motility. MATERIALS AND METHODS: The rats were randomly divided into five groups including: intact, sham, traumatic brain injury (TBI) group (intact rats under TBI), Celecoxib group (10 mg/kg), Ibuprofen group (10 mg/kg). Rats of the treatment groups received gavages at 1 hr before the TBI induction. The TBI was moderate and diffused using the Marmarou method. The gastric emptying and small intestine transit were measured by phenol red method. RESULTS: The gastric emptying didn’t change following TBI induction compared to intact group. The consumption of ibuprofen or celecoxib didn’t have any effect on gastric emptying compared to sham group. TBI induction didn’t have any effect on the intestinal transit. Also, there was no significant difference between ibuprofen or celecoxib consumption vs. sham group (P>0.05). CONCLUSION: The COX-2 selective inhibitor (celecoxib) or non-selective COX inhibitor (ibuprofen) have no effects on gastric or small bowel transit. Further work is necessary to investigate the effects of non-selective COX inhibitors and their impact on gastrointestinal motility disorders.